Role of Systemic Lupus Erythematosus Risk Variants With Opposing Functional Effects as a Driver of Hypomorphic Expression of TNIP1 and Other Genes Within a Three‐Dimensional Chromatin Network. Issue 5 (30th March 2020) - Pasula, Satish; Tessneer, Kandice L.; Fu, Yao; Gopalakrishnan, Jaanam; Pelikan, Richard C.; Kelly, Jennifer A.; Wiley, Graham B.; Wiley, Mandi M.; Gaffney, Patrick M.
Abstract : Objective: Genetic variants in the region of tumor necrosis factor–induced protein 3–interacting protein 1 ( TNIP1 ) are associated with autoimmune disease and reduced TNIP1 gene expression. The aim of this study was to define the functional genetic mechanisms driving TNIP1 hypomorphic expression imparted by the systemic lupus erythematosus–associated TNIP1 H1 risk haplotype. Methods: Dual luciferase expression and electrophoretic mobility shift assays were used to evaluate the allelic effects of 11 risk variants on enhancer function and nuclear protein binding in immune cell line models (Epstein‐Barr virus [EBV]–transformed human B cells, Jurkat cells, and THP‐1 cells), left in a resting state or stimulated with phorbol 12‐myristate 13‐acetate/ionomycin. HiChIP was used to define the regulatory 3‐dimensional (3‐D) chromatin network of the TNIP1 haplotype by detecting in situ long‐range DNA contacts associated with H3K27ac‐marked chromatin in EBV B cells. Then, quantitative reverse transcription–polymerase chain reaction (qRT‐PCR) was used to determine the expression of genes within the 3‐D chromatin network. Results: Bioinformatics analyses of 50 single‐nucleotide polymorphisms on the TNIP1 H1 risk haplotype identified 11 non–protein‐coding variants with a high likelihood of influencing TNIP1 gene expression. Eight variants in EBV B cells, 5 in THP‐1 cells, and 2 in Jurkat cells exhibited various allelic effects on enhancer activation, resulting in a cumulative suppressive effect on TNIP1 expression (net effect of risk variants −7.14 fold, −6.80 fold, and −2.44 fold, respectively; n > 3). Specifically, in EBV B cells, only 2 variants (rs10057690 and rs13180950) exhibited allele‐specific loss of both enhancer activity and nuclear protein binding (each P < 0.01 relative to nonrisk alleles). In contrast, the rs10036748 risk allele reduced binding affinities of the transcriptional repressors basic helix‐loop‐helix family member 40/differentially expressed in chondrocytes 1 (bHLHe40/DEC1) ( P < 0.05 relative to nonrisk alleles) and CREB‐1 ( P not significant) in EBV B cells, resulting in a gain of enhancer activity ( P < 0.05). HiChIP and qRT‐PCR analyses revealed that overall transcriptional repression of the TNIP1 haplotype extended to the neighboring genes DCTN4 and GMA2, both of which also showed decreased expression in the presence of the TNIP1 risk haplotype ( P < 0.001 and P < 0.01, respectively, relative to the nonrisk haplotype); notably, it was found that these genes share a 3‐D chromatin network. Conclusion: Hypomorphic TNIP1 expression results from the combined concordant and opposing effects of multiple risk variants carried on the TNIP1 risk haplotype, with the strongest regulatory effect in B lymphoid lineage cells. Furthermore, the TNIP1 risk haplotype effect extends to neighboring genes within a shared chromatin network.